CURRENT ISSUES OF PRESERVATION OF NATIONAL MUSICAL HERITAGE TRADITIONS (Innovate Conferences, 2025)
This article discusses the pressing challenges and necessary reforms related to the preservation and development of Uzbekistan's national musical heritage, particularly classical music traditions. The Uzbek maqom music, which has been preserved and passed down through generations for thousands of years, remains a central part of the nation's cultural identity. Recent governmental initiatives, including the presidential decree aimed at further developing Uzbek maqom art, highlight a renewed commitment to safeguarding this heritage. However, systemic issues persist, such as insufficient training duration in vocational education, a shortage of qualified traditional instrument instructors, and inconsistencies in the quality and dimensions of handcrafted instruments. The article identifies deficiencies in the existing infrastructure, including the lack of specialized departments for traditional performance in music schools and the need for standardized instrument production. It emphasizes the critical role of institutional reforms in education, curriculum enhancement, and the establishment of centralized facilities for instrument manufacturing and repair. Recommendations are provided to ensure continuity, quality, and cultural authenticity in the transmission of national music traditions to future generations.